2017
DOI: 10.1515/nor-2017-0393
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Crisis, and Social Media

Abstract: The literature on social media use in risk and crisis communication is growing fast, and it is time to take stock before looking forward. A review of 200 empirical studies in the area shows how the literature is indeed increasing and focusing on particular social media plat forms, users, and phases from risk to crisis relief. However, although spanning 40 countries, a large proportion of the world’s social media users are under-represented in the research. In addition, little attention is given to the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 52 publications
2
18
1
Order By: Relevance
“…Previous studies on risk, crisis and social media have shown that this area of research has been the subject of an increasing number of studies during the last decade, predominantly by U.S. and Western scholars; that they are characterized by quantitative approaches; and finally that many analyses concern the use of Twitter (see e.g., Rasmussen & Ihlen, 2017). The quantitative data in this study showed similar features overall (see also Figure 1).…”
Section: Systematic Analytical Work and Description Of Overall Quantisupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies on risk, crisis and social media have shown that this area of research has been the subject of an increasing number of studies during the last decade, predominantly by U.S. and Western scholars; that they are characterized by quantitative approaches; and finally that many analyses concern the use of Twitter (see e.g., Rasmussen & Ihlen, 2017). The quantitative data in this study showed similar features overall (see also Figure 1).…”
Section: Systematic Analytical Work and Description Of Overall Quantisupporting
confidence: 72%
“…It is not obvious, however, that this preponderance of U.S. studies will make the lessons less useful for global practitioners. Crisis communication research from an applied and strategic point of viewas with global academia in generalhas long been conducted in the United States, and less so in other parts of the world (see e.g., Rasmussen & Ihlen, 2017). The extensive U.S. research experience probably has led to high skill in performing studies and analyses developing advice and "best practice" recommendations for practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, scholars in the past years have increasingly paid attention to the SMCC research in contexts (Cheng, 2016a;Liu et al, 2015;Tai & Sun, 2007;Taylor & Perry, 2005;Zhu et al, 2017). This field also attracted updated reviews from several scholars such as Cheng (2016a), Eriksson (2018), and Rasmussen and Ihlen (2017). However, none of these studies fully examined the SMCC research in a non-Western context such as contemporary China and a review of the trends and research domains on SMCC in China is lacking.…”
Section: Social-mediated Crisis Communication (Smcc)mentioning
confidence: 99%
“…The studies included in this review all emphasized that radio was available and operational in situations with severely injured infrastructure, when the internet and mobile phones were not functioning. Also, studies suggest that people in emergencies and disasters tend to lean on information sources to which they are accustomed [20], and a large proportion of social media users were under-represented in the research [43]. Therefore, traditional radio still has an important role to play in disasters but may also be complimented by social media, mobile applications and other communication technology.…”
Section: Discussionmentioning
confidence: 99%